2018
DOI: 10.1186/s12014-018-9185-1
|View full text |Cite
|
Sign up to set email alerts
|

Label free quantitative proteomics reveals the role of miR-200b in androgen-independent prostate cancer cells

Abstract: Background: Our previous studies indicated that miR-200b inhibits the growth of androgen-independent prostate cancer (AIPC) cells. In this study, we employed quantitative proteomics techniques to unravel the role of miR-200b in AIPC. Results: Thirteen proteins were up-regulated in miR-200b mimics/mimics NC (negative miRNA control) and 14 proteins were down-regulated; 67 proteins were up-regulated in miR-200b inhibitor/inhibitor NC and 98 proteins were down-regulated. There were seven proteins which were both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…A liquid chromatography analysis of the protein regulated by miR-200b confirmed the findings presented by Asuthkar et al (2016). He et al (2018) used prostate cancer cell lines to demonstrate the involvement of transmembrane 4 L6 family member 1 (TM4SF1), yes-associated protein 1 (YAP1), Protein phosphatase inhibitor 2 (PPP1R2), Myristoylated alanine-rich C-kinase substrate (MARCKS), and Reticulon 4 (RTN4) inhibitors in reducing the progression of prostate cancer. The inhibitors analysed targeted the Wnt pathway.…”
Section: Targeting Metabolic Pathway Proteinssupporting
confidence: 60%
“…A liquid chromatography analysis of the protein regulated by miR-200b confirmed the findings presented by Asuthkar et al (2016). He et al (2018) used prostate cancer cell lines to demonstrate the involvement of transmembrane 4 L6 family member 1 (TM4SF1), yes-associated protein 1 (YAP1), Protein phosphatase inhibitor 2 (PPP1R2), Myristoylated alanine-rich C-kinase substrate (MARCKS), and Reticulon 4 (RTN4) inhibitors in reducing the progression of prostate cancer. The inhibitors analysed targeted the Wnt pathway.…”
Section: Targeting Metabolic Pathway Proteinssupporting
confidence: 60%
“…PC‐3, DU145, and LNCaP are prostate cancer cell lines that widely used in prostate cancer research. Cheng et al () reported that RTN4 was involved in the biological processes regulated by the androgen receptor, while He et al () label‐free quantitative proteomics study proved that RTN4 targeted by miR‐200b also played a role in androgen‐independent prostate cancer cells. Hence, we did not consider the androgen‐dependent or independent status of prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Label-free quantitation is easy to use, yields highly reproducible results, and is reliable [ 243 , 244 , 245 ]. It is cost-effective (avoids expensive chemical and metabolic tags) and allows the profiling of a number of large samples with the flexibility of multiple comparisons [ 246 , 247 ]. It eliminates the chance of variability that chemical labeling/tagging introduces and significantly reduces the sample preparation time by eliminating numerous steps [ 248 ].…”
Section: Advances In Proteomic Technologies Used In the Study Of Cancermentioning
confidence: 99%